Should R&D Champions be Protected from Foreign Takeovers? - Olivier Bertrand; Katariina Nilsson Hakkala; Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2008)
We analyze how the entry mode of Foreign Direct Investments (FDI) affects affiliate R&D activities. Using unique affiliate level data for Swedish multinational firms, we first present empirical evidence that acquired affiliates have a higher level of R&D intensity than greenfield (start-up) affiliates. This gap persists over time and with the age of the affiliates, as well as for different firm types and industries. To explain this finding, we develop an acquisition-investment-oligopoly model where we show that for a foreign acquisition to take place in equilibrium, the acquiring MNE must invest sufficiently in sequential R&D in the affiliate. Otherwise, rivals will expand their business, thus making the acquisition unprofitable. Two additional predictions of the model that foreign firms acquire high-quality domestic firms and that the gap in R&D between acquired and greenfield affiliates decreases in acquisition transaction costs are consistent with the data.
Keywords: F23; L10; L20; O30; 330; FDI; M&A; Multinational firms; R&D; Betriebliche Forschung; Übernahme; Multinationales Unternehmen; Direktinvestition; Schweden